The Impact of Chief Executive Officer Power on the Agency Costs: Evidence from Libya "An Applied Study on the Libyan Private Banks" - Moutaz A. Kablan (Communications of International Proceedings, 2021)
Given that the importance of stabilization of the agency theory as a base to organize the relationship between the shareholders "the origin" and the management "the agent" in the business environment nowadays, this study aimed to identify the impact of the chief executive officer "CEO" power on the agency costs in the Libyan private banks. To achieve this goal the study underlying the scarcity of related previous studies has stated its hypotheses. The study sample consists of (6) private banks for (5) years; then the study relied upon the multiple regression technique, which has been used to examine the fourth sub-hypotheses of the main one. As a result, the study became able to state that there is a positive significant relationship between the CEO ownership in the bank shares and the agency costs, while that there is no significant relationship between the duality of CEO role, the duration of CEO in his position, the independency of the board of directors and the agency costs in the Libyan private banks.
Keywords: Agency Costs – CEO Power – Agency Theory